Effect of Micronutrient Composition of Fish Feed to the Growth and Nutrient Content of Fishes: Cost-Efficient Production of Nutritious Fishes - Zaher, Mohammad Abduz; Islam, Mohua Sadia; Mamun, Sumaiya; Paul, Trisha (Bioresearch Communications, 2023)
Fish is the rich source of good quality protein. Per capita annual fish intake of Bangladesh is 21.90 kg and annual total need of fish is 42.38 lac mt. The current study's objective was to ascertain the nutritional value of various fish farmed in Bangladesh's Biofloc farm and regularly consumed by Bangladeshis by using nutrient rich formulated fish feed. The fish used in the study were tilapia fish (Oreochromis mossambicus) and shorputi fish (Systomus sarana). These fish species were cultured in a Biofloc setting. The edible portion of the samples had its composition closely investigated. The moisture, ash, and protein contents were determined using the AOAC-approved drying, Muffle-furnace, and Macro-Kjeldahl procedures, respectively. The edible proportion of fish in the current study ranged from 46.45 to 58.33%. The value for tilapia was the greatest (58.33%) while the value for shorputi was the lowest (46.45%). For some of the fish samples used in the investigation, the moisture content was found to be between 74.04 and 77.53%. Shorputi's lowest value was discovered to be 74.45%. For several fish samples, the ash concentration was determined to be between 1.04 and 1.31%. Shorputi had the greatest ash concentration (1.31%), while tilapia had the lowest (0.95%). Tilapia had a high protein content (23.77%). The study's most recent findings demonstrate that the farm formulated feed had a beneficial effect on the development and nutritional status of fish raised in biofloc systems. Bioresearch Commu. 10(1): 1453-1461, 2024 (January)